Relationship Attitude Natural Sciences To Responsibility In Junior High School - Tanti Tanti; Dwi Agus Kurniawan; Rahmi Putri Wirman; Rini Siski Fitriani; Nur Ika Sandi Pratiwi; Eva Yuhanis (Jurnal Pendidikan Sains Indonesia, 2020)
Education has a very important role in educating the life of the nation. Education should not only give birth to someone who is an expert in a particular field, but also includes how someone is able to bring themselves in a community, nation and state environment in accordance with applicable norms and rules. Therefore, the character of responsibility and attitude towards subjects is very important for every individual. However, education that is happening at this time still does not provide space for students to behave honestly because the learning process tends to teach moral education and character limited to the knowledge written in the text. Therefore this study was designed to see how the relationship between attitude and student responsibility towards science subjects especially junior high students. This study is a mix of correlational type associative method research. The procedure of this study began by following the procedure in stages. In the preparation stage, it is done by formulating the problem and its variables. Then a literature review is conducted, looking for supporting theories and deepening the discussion of the problem under study in order to obtain an overview of the research to be carried out as well as the instruments needed. At the stage of questionnaire data questionnaire data collection was given to 136 students in Adhyaksa 1 Junior High School, Jambi City. From the data, data analysis is then carried out, namely data coding, proper data collection and analysis of the data. The data analysis technique uses correlational tests to find out whether there is a relationship between attitude and responsibility. The results of this study indicate a relationship between attitude and responsibility with a Pearson Correlation value of 0.000 0.05 so that it can be concluded that there is a relationship between attitude and responsibility in Adhyaksa 1 Junior High School, Jambi City